Framework for integrating sustainability into the project planning process for buildings: The case of Malaysia / Nor Kalsum Mohd Isa - Mohd Isa, Nor Kalsum (2015)

(untitled)
The growth of urbanization in Malaysia has led to a greater demand of construction projects especially for building development. The demand has created pressure on the sustainability issues especially in urban area of the country. There are many efforts relating to sustainability integration in building projects have been implemented in Malaysia. Unfortunately, till now the issues of unsustainable building projects in the county are likely to persist. This denotes that there is a gap between the field of sustainability and the integration practices within Malaysian building projects. In the absent of a proper sustainability integration framework, thus, this research aims to develop an appropriate framework to integrate sustainability into the buildings’ project planning process towards delivering successful sustainable buildings in the country. Several research methodologies were used to achieve a thorough study for this research which are quantitative, qualitative and case study approach (mixed-methods). The findings of literature review were synthesized to formulate a preliminary framework of Integrating Sustainability into the Project Planning Process. The framework consists of the lists of sustainability principles of building (29 factors) and the strategies to integrate the principles into the project planning process (21 factors). The fifty (50) factors have gone through refining processes by involving 188 Malaysian project stakeholders. Quantitative survey was employed to elicit this knowledge. The framework was then brought into the case study and qualitative phase for further refining process and the external validation. The framework was also applied to the chosen three case study projects to identify the practicality. The final proposal devised at the end of this thesis comes in the form of a ‘Framework of Integrating Sustainability into the Project Planning Process’ with the remaining of 42 validated factors. The proposed framework will provide a better understanding to the project stakeholders on the sustainability principles of buildings and to expose them to the strategies to integrate the principles into the project planning process. Findings suggest significant connections exist between the level of project performances and the practices of the sustainability integration factors as proposed in the framework. It is remarkable that excellent performance of a sustainable building project is achieved when the sustainability principles are integrated efficiently into the project planning process. The thesis outcomes could provide an essential guide during the planning process towards delivering a successful sustainable building project in Malaysia in the future.